Metabolic profiling of tenacigenin B, tenacissoside H and tenacissoside I using UHPLC‐ESI‐Orbitrap MS/MS. (23rd May 2016) - Zhao, Can; Han, Ling‐Yu; Ren, Wei; Zhao, Hai‐Yu; Han, Shu‐Yan; Zheng, Wen‐Xian; Pang, Li‐Na; Li, Xiao‐Hong; Li, Ping‐Ping
Abstract: Marsdenia tenacissima, which is widely used as an anticancer herb in traditional Chinese medicine, has been shown to possess anticancer activity. However, its metabolic profile is poorly investigated. Tenacigenin B is the major steroidal skeleton of C‐21 steroids in M. tenacissima . Tenacissoside H and Tenacissoside I are detected at relatively high levels in M. tenacissima . Therefore, we studied their metabolic characteristics in human liver microsomes by ultra‐high‐performance liquid chromatography coupled with high‐resolution mass spectrometry. Fourteen metabolites were tentatively identified by accurate mass measurement and MS/MS fragmentation behavior. It was found that hydroxylation reactions were the major metabolic pathway of Tenacissoside H and Tenacissoside I in human liver microsomes, whereas the metabolic pathway of Tenacigenin B involved dehydrogenation reactions. This is the first time that the metabolic profile of C‐21 steroids from M. tenacissima has been explored in human liver microsomes, which is of great significance for subsequent pharmacokinetic and interaction research. Biotransformation in vivo or in vitro may influence the structure of a compound and change its activity. Identification of their fragmentation behaviors and metabolites provides valuable and new information for further understanding the anti‐tumor activity of M. tenacissima . Copyright © 2016 John Wiley & Sons, Ltd.